2020
DOI: 10.1371/journal.pone.0238766
|View full text |Cite
|
Sign up to set email alerts
|

Family planning awareness, utilization and associated factors among women of reproductive age attending psychiatric outpatient care, a cross- sectional study, Addis Ababa, Ethiopia

Abstract: Background Women with mental illness have a special need for family planning as they carry a high risk of unplanned pregnancy, sexual violence and, the poor obstetric outcomes due to their mental illness, as well as teratogenicity from exposure to psychotropic medications lower antenatal care utilization. Objective To assess knowledge, and utilization of family planning and associated factors among women attending psychiatric outpatient clinics in Addis Ababa. Methods A cross-sectional study was conducted amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The majority of these (n=13) focused on contraception use [28][40][43][51][53][71][74][75][2][90][94][105][106]. Four studies, which did not include a comparison, reported large proportions of women with SMI had never used contraception, had not used contraception during their most recent sexual experiences and had no intention of using contraception during sexual intercourse [87][109][71][93].…”
Section: Study Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these (n=13) focused on contraception use [28][40][43][51][53][71][74][75][2][90][94][105][106]. Four studies, which did not include a comparison, reported large proportions of women with SMI had never used contraception, had not used contraception during their most recent sexual experiences and had no intention of using contraception during sexual intercourse [87][109][71][93].…”
Section: Study Focusmentioning
confidence: 99%
“…Fourteen studies focused on pregnancy [23][24][43][46][66][87][88][91][41][92][95][108] [109][110]. Notably, the only two case studies included in this review were based around decision-making during pregnancy in the context of medication and abortion [23][43].…”
Section: Study Focusmentioning
confidence: 99%
“…10 In Ethiopia, half the women with MI used contraception, with 29.7% using oral hormonal contraception, 26.7% using injectables, and 22% using condoms. 11 Fears of drug interactions as well as a lack of knowledge influenced contraception use. 11 Barriers and facilitators to contraceptive use in women and contraceptive preferences in women with MI in the South African context are unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Fears of drug interactions as well as a lack of knowledge influenced contraception use. 11 Barriers and facilitators to contraceptive use in women and contraceptive preferences in women with MI in the South African context are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ethiopia has rigorous evidence on the prevalence of SMI from community studies (1.3%; 37.8% women), the impact of SMI on family planning has not been investigated in a comparative study [ 27 ]. In a study of women attending psychiatric outpatient care in Addis Ababa, Ethiopia's capital, only 68% of women with SMI were able to mention one family planning method and 38% of women expressed a low intention to use family planning in the future [ 28 ]. This is substantially lower than findings from a community study in the general population where 100% of women were aware of family planning methods, and 88% expressed favourable attitudes to using family planning [ 29 ] .…”
Section: Introductionmentioning
confidence: 99%